Impact of histological subtype on radiological and pathological response after neoadjuvant radiotherapy in soft tissue sarcoma. Issue 12 (December 2021) - Allignet, Benoît; Meurgey, Alexandra; Bouhamama, Amine; Karanian, Marie; Meeus, Pierre; Vaz, Gualter; Gouin, Francois; Moncharmont, Coralie; Prapant, Séverine; Waissi, Waisse; Sunyach, Marie-Pierre
Abstract: Background: Evaluation of response to neoadjuvant radiotherapy (NART) does not consider soft tissue sarcoma (STS) heterogeneity. We aimed to investigate radiological and pathological response of 4 major histotypes. Methods: Extremity or trunk STS patients who received 50 Gy NART between 2009 and 2020 were retrospectively included. Relative variation in tumor size (RVTS) and pathological response were reported in the overall population and in undifferentiated pleomorphic sarcoma (UPS), myxofibrosarcoma (MFS), myxoid liposarcoma (MLS) and synovial sarcoma (SS) patients to identify response modalities of each histotype. Results: Among the 121 included patients, 49, 19, 13 and 11 presented UPS, MFS, MLS and SS. Median RVTS were 0% (IQR -18-+18),  +8% (IQR 0-+24),  −12% (IQR -20–3) and −11% (IQR -15–9), respectively (p = 0.001). Median viable cells were 10%, 60%, 20% and 70% (p = 0.007). In overall population, pathological complete response and median necrosis were 27.7% and 10% without significant correlation to histotype (p = 0.18 and 0.06). Nineteen (38.8%) UPS specimens presented cysts that were emptied during the sampling process and distorted the microscopic response evaluation. Infiltrative growth pattern was observed in 28% and 38.9% UPS and MFS patients. Five (38.5%) MLS presented mature adipocytes without proven prognostic value. Cysts were observed in 36% of SS specimens. In the absence of initial tumor limits, the great viable cellularity of SS may be overestimated by their nodular aspect. Conclusion: After NART, we highlighted disparate response of UPS, frequent progression of MFS, and confirmed MLS and SS radiosensitivity. Response must be interpreted with caution and consider the histotype-specific patterns.